Pengaruh Rotasi Jabatan dan Motivasi Kerja terhadap Prestasi Kerja Pegawai di Pengadilan Agama Gorontalo Kelas 1A - Gansi, Nandito; Podungge, Robiyati; Monoarfa, Valentina (Economic Reviews Journal, 2024)
This research aims to determine how much influence position rotation and work motivation have on employee work performance at the Class 1A Gorontalo Religious Court. The method used in this research is a quantitative research method, with a sample size of 30 employees, and this research was conducted at the Gorontalo Class 1A Religious Court. To process data obtained from respondents, researchers used the SPSS application. The results of this research show that partially the independent variables (position rotation and work motivation) are only the work motivation variables that have a positive and significant effect, while the position rotation variable has no effect on the dependent variable (work performance). This is proven by the results of the t test. Meanwhile, in the results of the f test simultaneously the independent variables (position rotation and work motivation) have an effect on the dependent variable (work performance). Then based on the results of the coefficient of determination test (R2), the R Square value is (0.737) or (73.7%). This value shows that 73.7% of the dependent variable (work performance) can be influenced by independent variables (position rotation and work motivation) and 26.3% is influenced by other variables not examined in this research.